Search for extra dimensions using diphoton events in 7 TeV proton-proton collisions with the ATLAS detector* - Aad, Georges; Anders, Christoph; Anders, Gabriel; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Kasieczka, Gregor; Khomich, Andrei; Kluge, Eike-Erik; et al. (Physics letters, 2012)
Using data recorded in 2011 with the ATLAS detector at the Large Hadron Collider, a search for evidence of extra spatial dimensions has been performed through an analysis of the diphoton final state. The analysis uses data corresponding to an integrated luminosity of 2.12 fb−1 of s=7 TeV proton-proton collisions. The diphoton invariant mass (mγγ) spectrum is observed to be in good agreement with the expected Standard Model background. In the large extra dimension scenario of Arkani-Hamed, Dimopoulos and Dvali, the results provide 95% CL lower limits on the fundamental Planck scale between 2.27 and 3.53 TeV, depending on the number of extra dimensions and the theoretical formalism used. The results also set 95% CL lower limits on the lightest Randall-Sundrum graviton mass of between 0.79 and 1.85 TeV, for values of the dimensionless coupling k/M¯Pl varying from 0.01 to 0.1. Combining with previously published ATLAS results from the dielectron and dimuon final states, the 95% CL lower limit on the Randall-Sundrum graviton mass for k/M¯Pl=0.01 (0.1) is 0.80 (1.95) TeV.
ATLAS Collaboration: G. Aad, G. Anders, V. Andrei, Y. Davygora, T.A. Dietzsch, C. Geweniger, P. Hanke, M. Henke, G. Kasieczka, A. Khomich, E.E. Kluge, A. Kugel, V. Lendermann, R. Maenner, K. Meier, F. Müller, R. Narayan, S. Poddar, S. Schaetzel, V. Scharf, S. Schmitt, A. Schöning, N. Schroer, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und weitere]
Gesehen am 28.11.2018